Perancangan Aplikasi Presensi Berbasis Website Menggunakan Algoritma Convolutional Neural Network (CNN) Pada SMKN 4 Bekasi - Ronggo Sadewo; Andy Achmad Hendharsetiawan (Journal of Informatic and Information Security, 2023)
This research designs and implements a web-based attendance application using the Convolutional Neural Network (CNN) algorithm at SMK Negeri 4 Bekasi. The aim is to address common issues in manual attendance processes, namely, lack of efficiency and accuracy. The methods employed include designing a responsive website interface, implementing the CNN algorithm for facial recognition, and configuring an efficient data management system. Evaluation encompasses attendance accuracy, operational efficiency, and application responsiveness in real-world school environments. The research findings indicate that the web-based attendance application utilizing the CNN algorithm offers an effective solution for attendance recording at SMK Negeri 4 Bekasi.